Self-control and intimate partner violence: does gender matter? - Gulledge, Laura M. (Deviant behavior, 2023)
The present study focuses on the interrelationships among gender, self-control, and intimate partner violence (IPV). The extant bodies of literature suggest that both IPV and low self-control are gendered phenomena. That is, males tend to display lower mean levels of self-control than females, and there are notable differences in IPV between males and females. Since both phenomena are gendered, it is plausible that the relationship between self-control and IPV may also be gendered. To that end, the purpose of the present study is to explore the role played by gender in the relationship between self-control and IPV. To accomplish this, a sample of currently dating undergraduate and graduate college students (n = 960) was analyzed. The first objective is to determine whether self-control and IPV vary across gender. The second objective is to examine whether self-control predicts IPV differently by gender. Results indicated partial support for Gottfredson and Hirschi’s general theory of crime. Self-control operated similarly on IPV for both males and females, supporting the gender-neutrality of their theory. However, the interaction between gender and self-control did not significantly impact IPV offending. Moreover, the gender gap in crime as it relates to self-control remains in question as females were more likely than males to commit more types of IPV. Implications and directions for future research are discussed.